Public Man, Private Woman : Women in Social and Political Thought - Second Edition. - Elshtain, Jean Bethke (Princeton University Press, 1993)
Focusing on the Western philosophical tradition and the work of contemporary feminists, Jean Elshtain explores the general tendency to assert the primacy of the public world--the political sphere dominated by men--and to denigrate the private world--the familial sphere dominated by women. She offers her own positive reconstruction of the public and the private in a feminist theory that reaffirms the importance of the family and envisions an "ethical polity."